A Discussion Paper on Indigenous Custom Adoption Part 2: Honouring Our Caretaking Traditions - di Tomasso, Lara; de Finney, Sandrina (First Peoples Child & Family Review, 2015)
This paper forms Part 2 of a two-part discussion paper. Part 1 outlined a short history of adoption in Canada, examined the impact of forced, closed, and external adoptions on Indigenous adoptees and families, and traced the move toward more open statutory adoptions and greater cultural continuity in adoptions. Having zeroed in on the entangled histories of adoption and colonization in Part 1, here we explore traditional and contemporary practices of Indigenous custom adoption and caretaking. We first recount Western understandings and impositions, then feature Indigenous perspectives that centre spiritual and ceremonial protocols, values regarding child well-being and community connectedness, and the importance of kinship and customary forms of caretaking. We consider both the promises and complexities involved in designing and implementing custom adoptions, and the urgent need for adequate, equitable funding and supports to ensure their feasibility and sustainability. Finally, we highlight the resurgence of Indigenous authority over child welfare within a context of Indigenous self-determination and self-governance.